Death, New Land, and New Nature in Dostoevsky’s Novel The Idiot - Tatiana A. Kasatkina (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2020)
The article is dedicated to the analysis of the main concepts in the novel The Idiot aimed at a better understanding of its most enigmatic scenes. The main word of the novel is “new”, both on a plot level and on a deeper, ontological one. The novel vividly demonstrates how the manifestation of the “new” is actually connected with emotions that are very different from the ones we could suppose by default; in fact, it is connected with fear, disgust, a sense of disruption and destruction, radical transition, and unknown. Dostoevsky shows how this kind of human relationship with the “new” is an effective way to enclose man in the narrow prison of earthly life, denying immortality and resurrection; it also encloses man in the narrow prison of social prejudices, denying the possibility for free growth of his humanity. The analysis focuses on the first scene at the Epanchyns’, the story about the soldier Kolpakov (the only thing we know about the father of the prince), and Ippolit’s dream about the non-scorpion and the Newfoundland dog Norma.